The End of Grand Expectations: Monetary and Financial Integration After the Crisis in Europe - Heribert Dieter (Asian Development Bank (ADB), 2014)
The financial crisis in Europe has resulted in a new assessment of monetary and financial integration both in Europe and in Asia. Before the current crisis, regional integration in monetary and fiscal affairs including mechanisms to stabilize exchange rates enjoyed a lot of academic and political support. The crisis served as a reminder of the risks associated with monetary and financial integration and has resulted in a much more cautious appraisal. But despite the crisis, monetary and financial integration continues to be attractive. In particular, the facilitation of intra-regional trade through stable exchange rates and the potential development of joint lines of defense against financial volatility, e.g. a regional liquidity facility, are potential benefits of monetary and financial integration. However, the crisis in Europe has exposed a number of weaknesses in the approach taken in the eurozone. In Europe, there was an unresolved tension between the so-called no-bailout clause and the absence of an exit mechanism. In addition, participating economies that suffered from a high inflow of foreign capital, i.e. Ireland and Spain, were not able to (temporarily) restrict capital inflows, but had to bear the consequences. Thus, after the crisis in Europe the concept of monetary regionalism needed to be modified, but did not have to be discarded.
hdl:11540/1973
Keywords: F15; F33; F36; 330; European integration; monetary regionalism; financial integration; Treaty of Maastricht